Anti-soft rot and antioxidant behaviour of nine medicinal plants from Paya Bungor, Pahang / Nur Atikah Nabila Mohd Azli ...[et al.] - Mohd Azli, Nur Atikah Nabila; Harun, Aiza; Abdul Aziz, Noorshilawati; Daud, Shaari (Universiti Teknologi MARA Cawangan Pahang, 2021)
Medicinal plants have been gaining attention for their ability to control plant diseases. In searching of an alternative anti-soft rot agent from natural sources to substitute hazardous synthetic bactericides, we aimed to investigate the potential of plant extracts from nine medicinal plants from Paya Bungor, Pahang, as a potent anti-soft rot and antioxidant agent. Extracts were tested in-vitro against one phytopathogenic bacteria namely Erwinia chrysanthemi, a causal agent of soft rot disease. The antibacterial assay and antioxidant work were held using agar diffusion method and qualitative dot blot assay using 2,2-diphenyl-1-picrylhydrazyl (DPPH) reagent was used to screen antioxidant properties. Among the nine plant species, the methanol extract from Coscinium fenestratum (akar sekunyit) exhibited a marked inhibitory effect in-vitro on E. chrysanthemi pathogen with the inhibition zone of 19.67 mm. The antioxidative behavior could be seen in all types of the plant extracts. Therefore, the use of these plants against E. chrysanthemi to inhibit bacteria growth could be exploited in the future to replace chemical pesticides apart from antioxidative source. The data could be used as a basic scientific information to ensure the use of medicinal plant in traditional practice as well as the development of natural pesticides and medicines in future.